Strategi ekspansi bank syariah dalam mendorong pertumbuhan UMKM melalui peningkatan inklusi keuangan dan layanan digital - ’Ainunnaja, Isna (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the expansion strategy of Islamic banks in encouraging the growth of MSMEs through increasing financial inclusion and utilization of digital services. MSMEs are the backbone of the Indonesian economy, but often face challenges such as limited access to capital and financial literacy. Sharia banks have a strategic role in providing access to sharia-based financing that is free from interest, making it more accessible to MSME players. In addition, the development of digital services, such as fintech and mobile banking, allows Islamic banks to reach more MSMEs, including those in remote areas, with fast and efficient processes. This research was carried out through a literature study by reviewing various relevant sources. The research results show that financial inclusion and digitalization of financial services can increase MSMEs’ access to financing, support business growth, and increase their competitiveness. However, challenges such as low financial literacy and limited digital infrastructure require special attention through education and government support.